Factors associated with quality of care for patients with pancreatic cancer in Australia. Issue 10 (21st November 2016) - Burmeister, Elizabeth A; O'Connell, Dianne L; Jordan, Susan J; Goldstein, David; Merrett, Neil; Wyld, David K; Beesley, Vanessa L; Gooden, Helen M; Janda, Monika; Neale, Rachel E
Abstract: Objectives: To develop a composite score for the quality of care for patients with pancreatic cancer in Australia; to determine whether it was affected by patient and health service‐related factors; to assess whether the score and survival were correlated. Design, participants and setting: We reviewed medical records of patients diagnosed with pancreatic cancer during July 2009 – June 2011 and notified to the Queensland and New South Wales cancer registries. Design and main outcome measures: Participants were allocated proportional quality of care scores based on indicators derived from a Delphi process, ranging from 0 (lowest) to 1 (highest quality care). Associations between patient and health service‐related factors and the score were tested by linear regression, and associations between the score and survival with Kaplan–Meier and Cox proportional hazards methods. Results: Proportional quality of care scores were assigned to 1571 patients. Scores for patients living in rural areas were significantly lower than for those in major cities (adjusted difference, 11%; 95% CI, 8–13%); they were higher for patients in the least socio‐economically disadvantaged areas ( v most disadvantaged areas: 8% higher; 95% CI, 6–11%), who were younger, had better Eastern Cooperative Oncology Group performance status, or who first presented to a hospital with a high pancreatic case volume. Higher scores were associated with improved survival; after adjusting for patient‐related factors, each 10 percentage point increase in the score reduced the risk of dying by 6% (hazard ratio, 0.94; 95% CI, 0.91–0.97). Conclusion: Geographic category of residence may influence the quality of care received by patients with pancreatic cancer, and survival could be improved if they received optimal care.